Genetic and biochemical diversity among Trichoderma isolates in soil samples from winter wheat fields of the Great Hungarian Plain - Kredics, László (Acta Biologica Szegediensis, 2012)
One hundred and sixteen Trichoderma isolates were collected from chopped roots of winter wheat of five agricultural fields in the Great Hungarian Plain. The isolates were identified by the sequence analysis of the internal transcribed spacer (ITS) region with TrichOKEY 2.0 and BLAST similarity searches. The Trichoderma species detected in the samples were T. atroviride, T. brevicompactum, T. gamsii, T. harzianum, T. koningiopsis/T. ovalisporum, T. longibrachiatum/H. orientalis, T. pleuroticola, T. rossicum, T. spirale, T. tomentosum/T. cerinum and T. virens. Beneficial taxa widely used as biocontrol agents against plant pathogenic fungi (e.g. T. harzianum, T. virens, T. atroviride) could be isolated from the samples examined during this study, indicating that the winter wheat rhizosphere may be a rich source of potential biocontrol isolates. Several species could be characterized with well-defined isoenzyme patterns during cellulose-acetate electrophoresis, suggesting that this method can be used for the analysis of biochemical diversity between and within particular species of the genus Trichoderma.